Academic Ethics and Law Education - Daskalov, Valchin (Research Papers, 2014)
This work is dedicated to the moral-ethics basis of the relationships between the members of the academic community of the UNWE, related to the teaching of law disciplines. The first starting point of the study is the general term “academic ethics”. The content of this term has been outlined, its juridical basis is being analyzed and conclusions on the social existence of this phenomenon in the current reality have been made. With regard to this the most important characteristics of the Ethics code of the UNWE have been summarized. The second starting point of the study are the peculiarities of the classic legal professions – magistrate; lawyer; public prosecutor and their impact on the educational process. The two social phenomena outlined, along with their independent existence, closely interlace with each other in the everyday life of a Law faculty. This justifies the use of a classic inductive approach: on the basis of the examination of the typical own characteristics of both phenomena and the ascertaining of their crossing points and mutual impact, general conclusions and assumptions are drawn. In the light of the defined issues, the study analyzes the reflections of the characteristics of the law education on the contents of the academic ethics. A short survey of the general moral-ethics obligations of the subjects, participating in the complex process of the law high education and the consequences of their violations has been made.
Keywords: Academic ethics; Course report; “Law” discipline; Educational process; Higher education act; Act on the development of the academic staff in Republic Bulgaria; Ethics code of the UNWE (University of National and World Economy); Plagiarism; Conflict of values and interests; Academic ethics commission; Academic community; Classes; Supervision of the knowledge; Scientific correctness; Case solving